2005
DOI: 10.1254/jphs.fpj05007x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adrenomedullin on Adrenergic Vasoconstriction in Mesenteric Resistance Arteries of the Rat

Abstract: Abstract. Adrenomedullin (AM) is a hypotensive peptide that belongs to a family of peptides structurally related to calcitonin gene-related peptide (CGRP). The present study examined the effect of AM on adrenergic nerve-mediated vasoconstriction in rat perfused mesenteric vascular beds without endothelium. Perfusion of AM at 0.1 nM but not 10 nM increased vasoconstrictor responses to periarterial nerve stimulation (PNS) (1 -4 Hz), while AM at 10 nM significantly attenuated vasoconstriction induced by bolus inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…In this study, the inhibitory effects of adrenomedullin on the depolarization-induced contraction were blocked by the receptor antagonist CGRP 8–37 , but not by adrenomedullin 22–52 . In the perfused rat mesenteric artery, adrenomedullin at low concentrations (0.1 n M ), but not higher concentrations, potentiated adrenergic vasoconstriction by inhibiting neurotransmission of CGRP-containing nerves, which counteract adrenergic nerve-mediated vasoconstriction [18]. However, in this study, adrenomedullin had inhibited the contraction induced by depolarization by external high potassium.…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, the inhibitory effects of adrenomedullin on the depolarization-induced contraction were blocked by the receptor antagonist CGRP 8–37 , but not by adrenomedullin 22–52 . In the perfused rat mesenteric artery, adrenomedullin at low concentrations (0.1 n M ), but not higher concentrations, potentiated adrenergic vasoconstriction by inhibiting neurotransmission of CGRP-containing nerves, which counteract adrenergic nerve-mediated vasoconstriction [18]. However, in this study, adrenomedullin had inhibited the contraction induced by depolarization by external high potassium.…”
Section: Discussioncontrasting
confidence: 54%
“…Beyond itsaction on endothelial permeability, AM comprises important effects on the vasculars ystem. Cumulating evidence demonstratesincreased nitricoxide release, vasodilatationindifferent vascularbeds, andsubsequent hypotension due to AM (95,99,104,114,(126)(127)(128)(129)(130). With respect to hypotension in severe infection andsepsisitisnoteworthy that septicmice over-expressing AM in their vasculatureare resistanttoendotoxin shockdespitehypotension (127).…”
Section: Adrenomedullin -Actiononthe Endothelium Andvascular System Bmentioning
confidence: 99%
“…Akiyama et al, (24) demonstrated that endo CL internalization as a result of AM introduction could be blocked by both AM and CGRP antagonists (AM22-52 and CGRP8-37) and that desensitized receptor due to binding to AM was also desensitized against CGRP. Akiyama et al (25) suggested that, the receptor was desensitized against both of these two peptides, regardless of with which it encounters. Also previous studies revealed that AM presynaptically inhibits the neurotransmission of rat mesenteric resistance arteries in perivascular CGRPergic nerves, possibly by reducing CGRP release.…”
Section: Discussionmentioning
confidence: 99%